Effectiveness of Hybrid Learning Assisted in e-Learning Media in Mathematics Learning at Elementary School - Muhammad Mushfi El Iq Bali; Zulfatul Aliyah; Didik Humaidi (Journal of Innovation in Educational and Cultural Research, 2022)
This study describes the effectiveness of hybrid learning using e-learning media during the Covid-19 pandemic, especially in mathematics. This research is descriptive quantitative research using a survey method, focusing on learning evaluation using e-learning media. The research population was all students of Madrasah Ibtidaiyah Miftahul Huda Pedaganga Tiris Probolinggo who were taught mathematics using hybrid learning methods. The research sample is the sixth-grade students of Madrasah Ibtidaiyah Miftahul Huda Pedaganga Tiris Probolinggo who were selected using a simple random sampling technique considering the homogeneity of the population. The data collection instrument used a hybrid learning questionnaire. Data analysis used descriptive statistics. The results of the study describe students assessing mathematics learning using e-learning media as very effective. Although there are also students who consider hybrid learning ineffective, absolutely no one considers it very ineffective. Based on the results of the analysis and research findings regarding the effectiveness of the implementation of hybrid learning using e-learning madrasah in mathematics subjects, it shows that learning using e-learning madrasah is quite effective to implement. This is because many parties support this learning, but several factors can hinder learning, so it must be considered so that learning can run smoothly.